Cyanobacteria North of 60°: Environmental DNA Approaches - Alambo, Katherine I. (Université d'Ottawa / University of Ottawa, 2017)
Cyanobacterial blooms, such as those recently reported in Great Slave Lake (GSL, NWT), have sparked concern over the occurrence of toxic blooms in the North. This study investigated past and present incidences of cyanobacteria in lakes above latitude 60° N. The abundance of the toxin (microcystin) gene mcyE, as well as genes common to all cyanobacteria (16S rRNA) and bacteria (glnA) were quantified from lake sediment cores using ddPCR. Individual colony isolates from a surface bloom in Yellowknife Bay (GSL) in August 2015 were amplified and identified as non-toxigenic Dolichospermum lemmermannii. Very low levels of microcystin genes were detected through the sediment archives (over ~100-150 yr) of GSL and other lakes, as well as in the plankton of GSL. While recent increases in mcyE were not observed, an increase in the cyanobacterial 16S rRNA and glnA genes was seen through time. In the high Arctic Meretta Lake, gene abundance profiles reflected the effects of past eutrophication and recovery.